Prediction of new onset atrial fibrillation in patients with acute pulmonary embolism: The role of sPESI Score - Ekrem Şahan; Suzan Şahan; Murat Karamanlıoğlu; Murat Gül; Omaç Tüfekçioğlu (KARE Publishing, 2019)
Objective: Acute pulmonary embolism (APE) is a serious clinical situation and atrial fibrillation (AF) is the most common arrhytmia in clinical practice. The Pulmonary Embolism Severity Index (PESI) is an accepted risk stratification tool used to predict short term mortality in APE. The aim of this study was to evaluate the relationship between the PESI score and new-onset AF in patients with APE. Methods: The records of 869 APE patients admitted between May 2012 and December 2015 were evaluated retrospectively. The PESI score was calculated for every patient. Clinical variables associated with new-onset AF in APE were assessed after the exclusion of patients with hypertension, coronary or hemodynamically significant valvular heart disease, hepatic or renal dysfunction, chronic obstructive pulmonary disease, thyroid dysfunction, diabetes mellitus, sleep apnea, any history of inflammatory or infectious disease, or recent trauma. New-onset AF was detected in 42 (4.8%) patients. Results: Age, gender, systolic and diastolic blood pressure, heart rate, fasting glucose level, serum creatinine, left ventricle ejection fraction, tricuspid annular plane systolic excursion value, and pulmonary artery systolic pressure measures were not significantly different between patients with and without AF. New-AF patients demonstrated larger LVEDD and LAD dimensions (p <0.001 for both). The PESI score was higher in the new-onset AF group (93+-23 vs.75+-17; p <0.001). LVEDD, LAD, levels of uric acid, bilirubin, albumin, and troponin, and PESI score were univariate predictors of new-onset AF. Conclusion: In patients with APE, the PESI score was positively correlated with new-onset AF. A PESI score greater than 82.50 may be useful to predict new-onset AF in these patients.